Introductory Algebra for College Students (7th Edition)

Published by Pearson
ISBN 10: 0-13417-805-X
ISBN 13: 978-0-13417-805-9

Chapter 6 - Section 6.5 - A General Factoring Strategy - Exercise Set - Page 462: 56



Work Step by Step

$-7y^{3}+21y^{2}-14y\qquad$...factor out the common term, $-7y$ $=-7y(y^{2}-3y+2)$ Two factors of $ac=2$, whose sum is $b=-3$ are $-1$ and $-2$. Rewrite the middle term and factor in pairs. $-7y(y^{2}-3y+2)$ $=-7y(y^{2}-y-2y+2)$ $=-7y[y(y-1)-2(y-1)]\qquad$...factor out the common binomial factor,$y-1$. $=-7y(y-1)(y-2)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.